Exploring doctorate holders’ perceptions of the non-academic labour market and reputational problems they relate to their employment - Suomi Kati; Kuoppakangas Päivikki; Kivistö Jussi; Stenvall Jari; Pekkola Elias (Springer, 2022)
Doctoral employment outside universities has been increasing, as universities cannot employ all doctorate holders. Nevertheless, it has been argued that the shift from doctoral programs to the non-academic labour market has been limited. In this qualitative study, more than 800 verbal answers given by doctorate holders to a pair of open-ended questions were content-analysed to explore doctorate holders’ perceptions of the nonacademic labour market and the reputational problems they relate to their employment. The study identifies four reputational problems which doctorate holders relate to their employment: the oversupply problem, the overeducation problem, the consistency problem and the communication problem. By identifying potential reputational problems on the doctorate holders level, this research contributes novel information in terms of both theory development and practitioner insights.